Do eu ao mundo: a formação pessoal - profissional a partir do olhar subjetivo de uma aluna - monitora - professora da dança - ALFAIA, Tifany Souza de (2019)
The theme of this research is related to my experiences as a dance student – monitor - in projects, dance schools and fitness centers. In this learning I pointed out what I considered negative aspects and, later, what became positive points in the challenge of being student and, afterwards, dance teacher. This work aims to consider and analyze the teaching-learning relationship in dance, with the didactic and methods applied by teachers with whom I had contact in the particularity of this teaching. In my conceiving I learned about errors and hits, with qualified and not so much qualified teachers; however, I realized that some teachers also learn as they teach and that therefore there is no recipe for teaching, but a continuous discovery in the exercise of one's own doing. In this practice, what would be the positive and negative points in the transition from being a student to being a dance teacher? What didactic challenges did the student who quickly becomes a teacher have to overcome? Here are some questions that I believe I will answer in this study. For better speculation and analysis of this research object, I chose the authors Paulo Freire, who states that every action has a purpose just like educating (2003), Maria Abrahão and Carmen Eckhardt with the wonderful thought that error is not so bad, but a temporary form of knowing (2004), Márcia Strazzacappa, for a much more critical dance that does not reproduce standards imposed by society (2003). The methodological path of this research articulates the auto-ethnographic method, in which the researcher takes a look at his or her own formation, seeking to understand in a more conscious way the trajectory of his / her teaching-learning process as a student and sometimes as a teacher while still a student.